Six new species of the genus Armandia Filippi, 1861 (Polychaeta, Opheliidae) from Lizard Island (Great Barrier Reef, Australia) - Parapar, Julio; Moreira, Juan (Zootaxa, 2015)
From the study of the material collected during the Polychaete Workshop held in Lizard Island (Great Barrier Reef, Australia) in August 2013, six species belonging to the genus Armandia (Polychaeta, Opheliidae) are newly described. Armandia bifida n. sp. is characterised by the bifid shape of the prechaetal lobe in CH1–CH3, A. dolio n. sp. by the barrel-shaped anal (=pygidial) tube (=funnel), A. filibranchia n. sp. by the extremely long and thin branchiae, A. laminosa n. sp. by the foliose shape and large size of the prechaetal lobe in CH1–CH3, A. paraintermedia n. sp. by the squared-shaped anal tube and size and shape of anal cirri, and A. tubulata n. sp. by the tubular shape of the anal tube. All species are fully described and illustrated, and compared with similar species. Several body characters of taxonomic relevance (e.g., anal tube and parapodia shape) are studied based on SEM micrographs. A key of the Armandia species hitherto described or reported in South-East Asia and Australasia is provided based on features of the anal tube.
World Polychaeta Database (WPolyDb). Open access at Zootaxa